2023
DOI: 10.3390/ijms24129981
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Circulating Cell-Free DNA (cfDNA) as a Biomarker of the Development and Evolution of Periodontitis

Abstract: In the last few decades, circulating cell-free DNA (cfDNA) has been shown to have an important role in cell apoptosis or necrosis, including in the development and evolution of several tumors and inflammatory diseases in humans. In this regard, periodontitis, a chronic inflammatory disease that can induce the destruction of supporting components of the teeth, could represent a chronic inflammatory stimulus linked to a various range of systemic inflammatory diseases. Recently, a possible correlation between per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Positively charged nanoparticles known as cationic nanomaterials function as cell-free nucleic acid scavengers to reduce inflammation in tissues [ 164 ]. In patients with periodontitis, the level of cell-free DNA (cfDNA) in the gingival sulcus fluid correlates with the degree of periodontitis [ 165 ]. For this reason, Huang et al [ 111 ] designed a cfDNA scavenger.…”
Section: Biomaterials Regulate Macrophage Polarizationmentioning
confidence: 99%
“…Positively charged nanoparticles known as cationic nanomaterials function as cell-free nucleic acid scavengers to reduce inflammation in tissues [ 164 ]. In patients with periodontitis, the level of cell-free DNA (cfDNA) in the gingival sulcus fluid correlates with the degree of periodontitis [ 165 ]. For this reason, Huang et al [ 111 ] designed a cfDNA scavenger.…”
Section: Biomaterials Regulate Macrophage Polarizationmentioning
confidence: 99%
“…In association with the development of the immune response in patients, changes occur in the connective tissue and bone tissue with cellular activation. In cases of moderate to severe periodontitis, the destruction of the gum tissue and local and systemic in ammatory reactions lead to the emergence of oxidative stress in patients (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Present in various bodily fluids, cfDNA concentrations fluctuate with tissue damage, cancer, and inflammation, making it a valuable noninvasive biomarker for diagnosing and prognosticating various diseases. In tissues, cfDNA is involved in the progression of several inflammatory-related diseases, such as periodontitis, inflammatory bowel disease, and rheumatoid arthritis. Recent studies have revealed a significant increase in cfDNA levels in patients with osteoarthritis, where inhibition of cfDNA has been linked to reduced cartilage damage . Therefore, cfDNA may play a crucial role in the inflammatory development of TMJ OA; however, the specific pathogenic mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%